2007
DOI: 10.1194/jlr.d600034-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid characterization of the fatty acyl composition of complex lipids by collision-induced dissociation time-of-flight mass spectrometry

Abstract: Profiling of leaf extracts from mutants of Arabidopsis with defects in lipid desaturation demonstrates the utility of collision-induced dissociation time-of-flight mass spectrometry (CID-TOF MS) for screening biological samples for fatty acid compositional alterations. CID-TOF MS uses the collision cell of a quadrupole time-of-flight mass spectrometer to simultaneously fragment all of the ions produced by an ionization source. Electrospray ionization CID-TOF MS in the negative mode can be used to analyze fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Furthermore, the Q-TOF analysis indicated that these oxidized species, 18:4-O, 18:3-O, and 18:2-O, are the major and generally the only lipid fragments with nominal m/z of 291, 293, and 295 (Buseman et al, 2006;Esch et al, 2007). The level of oxylipin-containing lipid molecular species was quantified by precursor scanning of oxylipin acyl anions, m/z 291, 293, and 295, using a triple quadrupole mass spectrometer (API 4000; Applied Biosystems) in the negative mode.…”
Section: Oxidized Lipid Analysismentioning
confidence: 99%
“…Furthermore, the Q-TOF analysis indicated that these oxidized species, 18:4-O, 18:3-O, and 18:2-O, are the major and generally the only lipid fragments with nominal m/z of 291, 293, and 295 (Buseman et al, 2006;Esch et al, 2007). The level of oxylipin-containing lipid molecular species was quantified by precursor scanning of oxylipin acyl anions, m/z 291, 293, and 295, using a triple quadrupole mass spectrometer (API 4000; Applied Biosystems) in the negative mode.…”
Section: Oxidized Lipid Analysismentioning
confidence: 99%
“…To achieve this quantitative measure for this large number of molecular species, it was necessary to separate and to employ a different separation protocol that was ideal for each individual class of lipid. Lipidomic analyses of yeast (23), Caenorhabditis elegans (24), tuberculosis mycobacteria (25), human plasma (26), and others (27) have emerged.…”
Section: Lipidomic Studiesmentioning
confidence: 99%
“…Lipids were rendered visible under UV light by exposure to 0.005% (w/v) primulin in 80% (v/v) acetone, after which the individual lipid classes were collected and their fatty acid content determined by gas chromatography. For lipidomics analysis, lipids were extracted according to the instructions provided by the Kansas Lipidomics Research Center (http://www.k-state.edu/lipid/lipidomics/), and PG molecular species were quantified by analysis performed at that facility (Esch et al, 2007). Lipid molecular species for the single lipids were reanalyzed, and the content of all molecular species in specific lipids was set as 100%.…”
Section: Lipid Extraction and Analysismentioning
confidence: 99%